(3GbJUGOjGJ GdeGdjI GdYGeI (B:s (3eONd MOjK (B/s - (3GdHfG, eMeOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2009)
(3OhQ GdOhdI aj GdfTGW GdGbJUGOj(B- (3eaghe GdehGRfI GdYGeI(B- (3GdfTGW GdGbJUGOj ddOhdI(B- (3GdSjGSI GdeGdjI ddOhdI(B- (3GdGjQGOGJ GdYGeI ddOhdI(B- (3eUGOQ GdGQGOGJ GdYGeI(B- (3GdJfXje Gdafj ddVQjHI(B- (3fXQjI VQjHI GdONd(B- (3GdGKGQ GdGbJUGOjI ddVQjHI(B- (3GdfabGJ GdYGeI ddOhdI(B- (3GdfabGJ GdYGeI(B- (3GdfabGJ GdJMhjdjI h GdOYe(B- (3GdOYe GdMchej ddabQGA aj eUQs
Keywords: (3GdEbJUGOs; (3GdGbJUGO GdeGdjs; (3GdeGdjI GdYGeIs